Collaborating With Families to Address Cyberbullying: Exploring School Counselors' Lived Experiences. Issue 1 (1st November 2021) - Su, Yi-Wen; Doty, Jennifer; Polley, Bella R.; Cakmakci, Huzeyfe; Swank, Jacqueline; Sickels, Allison
Limited research has focused on exploring the collaboration between home and school to address cyberbullying. In this qualitative study, we interviewed 17 school counselors to explore their experiences working with parents and caregivers in addressing cyberbullying. We identified four themes: (a) connections with parents and families, (b) digital citizenship, (c) blurred boundaries, and (d) family/counselor support. We discuss the themes and offer implications for school counselors to address cyberbullying in schools, including highlighting strategies for bridging the gap between families and schools through policies and communication about cyberbullying.